Patch exploitation by non‐aggressive parasitoids under intra‐ and interspecific competition. Issue 1 (20th March 2016) - Robert, Félix‐Antoine; Brodeur, Jacques; Boivin, Guy
Abstract: The behavioral strategies evolved by insect parasitoids to optimize their foraging efforts have been the subject of many theoretical and empirical studies. However, the effects competition may have on these strategies, especially for species that do not engage in antagonistic behaviors, have received little attention. The objective of this study was to evaluate the effects of intraspecific and interspecific competition on patch exploitation strategies by two non‐aggressive species, Trichogramma pintoi Voegelé and Trichogramma minutum Riley (Hymenoptera: Trichogrammatidae), both generalist egg parasitoids. We analyzed the patch residence times of females, their patch‐leaving mechanisms, and the sex allocation of their progeny while foraging either alone, with an intraspecific competitor, or with an interspecific competitor. To some extent, each species responded differently to the presence of a competitor in the patch. Trichogramma pintoi females did not change their patch‐leaving mechanisms in response to competition and behaved as if under an exploitative competition regime, whereas T. minutum females did change their patch‐leaving mechanisms in response to competition and remained longer in the host patch than expected. Antennal rejection, and not oviposition, was the proximate behavioral mechanism underlying patch‐leaving decisions by both species. Neither species adjusted the sex allocation of their progeny in response to competition. These results indicate that the effects of competition differ even among closely related parasitoid species.